Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/annonc/mdu106
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of probiotics in people with cancer: a systematic review

Abstract: Probiotics may be a rare cause of sepsis. Further evidence needs to be collated to determine whether probiotics provide a significant overall benefit for people with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 32 publications
3
100
2
4
Order By: Relevance
“…Amazingly, the probiotic group obviously reduced the incidence of CTC grade ⩾ 2 diarrhea, (OR = 0.36; 95% CI 0.21-0.59; Po0.0001), also demonstrated in the meta-analysis of Redman et al 22 However, the effect of probiotics was not so significant for reducing incidence of CTC Grade ⩾ 3 diarrhea, as the OR is 0.35 (95% CI 0.13-0.96; P = 0.04), and that, for subgroup analysis, it is also unclear for RID (OR = 0.37, 95% CI 0.09-1.60; P = 0.19) and for CID (OR = 0.40, 95% CI 0.15-1.03; P = 0.06).…”
Section: Efficacysupporting
confidence: 53%
See 3 more Smart Citations
“…Amazingly, the probiotic group obviously reduced the incidence of CTC grade ⩾ 2 diarrhea, (OR = 0.36; 95% CI 0.21-0.59; Po0.0001), also demonstrated in the meta-analysis of Redman et al 22 However, the effect of probiotics was not so significant for reducing incidence of CTC Grade ⩾ 3 diarrhea, as the OR is 0.35 (95% CI 0.13-0.96; P = 0.04), and that, for subgroup analysis, it is also unclear for RID (OR = 0.37, 95% CI 0.09-1.60; P = 0.19) and for CID (OR = 0.40, 95% CI 0.15-1.03; P = 0.06).…”
Section: Efficacysupporting
confidence: 53%
“…As Redman et al 22 reported in a previous systematic review, there was a wide range of AEs for using probiotics in patients with cancer, 'including: bacteraemia/fungaemia, infection, GI symptoms (diarrhoea, constipation, dysphagia, nausea and vomiting), urinary symptoms (only present in patients with transitional cell carcinomas), sicchasia, raised blood pressure and raised intra-cranial pressure'. Because of the heterogeneity of the different treatment regimes and malignancies, the AEs associated with probiotics could not be distinguished.…”
Section: Safetymentioning
confidence: 92%
See 2 more Smart Citations
“…Good evidence in both animal and human studies support that probiotics, prebiotics and synbiotics have a role in the prevention of mucositis during chemotherapy, and that they rarely cause sepsis 86 receptors 99 and, therefore, this finding suggests that the microbiota is a legitimate target for the treatment of patients with metastatic disease. Secondly, it also suggests that there is a role for selective antibiotic use, and that retired compounds can be repurposed for engineering the microbiota.…”
Section: [H2] Dietary Interventionsmentioning
confidence: 99%